2019
DOI: 10.1002/jctb.6125
|View full text |Cite
|
Sign up to set email alerts
|

Non‐thermal plasma‐assisted catalytic oxidation of NO in a dielectric barrier discharge reactor packed with MOx/Al2O3 (M = Mn or Co) as catalysts

Abstract: BACKGROUND Plasma catalysis has emerged as a powerful tool in converting a gas or gas mixture into other value‐added or environment‐friendly chemicals. However, a substantial research effort is needed to further understand the physical and chemical interactions between plasma and catalysts, and their contribution to the chemical reactions. RESULTS For a given energy density (ED) of 535 ± 25 J L−1, a dielectric barrier discharge (DBD) reactor packed with Al2O3 achieved higher NO2 selectivity and N2O concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…When SED was more than 303.6 J L -1 , the conversion efficiency decreased with the increase of SED, which was mainly attributed to the existence of Equation ( 4). [1] In this case, the produced NO 2 Small 2022, 18, 2106680…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…When SED was more than 303.6 J L -1 , the conversion efficiency decreased with the increase of SED, which was mainly attributed to the existence of Equation ( 4). [1] In this case, the produced NO 2 Small 2022, 18, 2106680…”
Section: Resultsmentioning
confidence: 97%
“…As presented in Figure 4d, the firm peaks around 3447 and 1638 cm −1 could be attributed to the stretching vibration of the combination of hydroxyl groups and OH of the physically adsorbed water. [1] The results showed that the vibration frequencies of SO 3…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations